2016
DOI: 10.1186/s12263-016-0533-3
|View full text |Cite
|
Sign up to set email alerts
|

Metallothioneins 1 and 2, but not 3, are regulated by nutritional status in rat white adipose tissue

Abstract: BackgroundCumulating evidence underlines the role of adipose tissue metallothionein (MT) in the development of obesity and type 2 diabetes. Fasting/refeeding was shown to affect MT gene expression in the rodent liver. The influence of nutritional status on MT gene expression in white adipose tissue (WAT) is inconclusive. The aim of this study was to verify if fasting and fasting/refeeding may influence expression of MT genes in WAT of rats.ResultsFasting resulted in a significant increase in MT1 and MT2 gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…Mt3 mRNA in the liver was not considered expressed since the ΔCt values were much higher compared with Mt1 and Mt2 ( Appendix A , Table A2 ). This finding coincides with several previous reports of Mt3 gene and protein expression being absent in mouse and rat liver [ 14 , 15 , 34 , 35 ]. The qPCR Ct values for β- actin that were used for target gene normalization are reported in Appendix A , Table A5 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Mt3 mRNA in the liver was not considered expressed since the ΔCt values were much higher compared with Mt1 and Mt2 ( Appendix A , Table A2 ). This finding coincides with several previous reports of Mt3 gene and protein expression being absent in mouse and rat liver [ 14 , 15 , 34 , 35 ]. The qPCR Ct values for β- actin that were used for target gene normalization are reported in Appendix A , Table A5 .…”
Section: Resultssupporting
confidence: 93%
“…Moreover, MT-1/2-deficient mice are more susceptible to neuronal damage associated with kainic acid (KA)-induced seizures [ 12 ]. In mammals, MT-1 and MT-2 (MT-1/2) expression is ubiquitous, whereas MT-3 is mainly localized to the brain but is expressed to a lesser degree in other organs [ 13 , 14 , 15 ]. MT-4 expression is largely confined to stratified epithelial cells associated with skin, esophagus, and the stomach [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, MTs seem to prevent high‐fat diet‐induced obesity and MT gene expression in mice liver is influenced by fasting/refeeding, being increased by fasting . Similar results were also found in rat adipose tissue …”
Section: Discussionsupporting
confidence: 73%
“…[ 31 , 32 ] MTs were induced by treatment with dexamethasone and activators of the cAMP/PKA pathway, i.e., forskolin and bromo-cAMP, in rat adipocytes. [ 15 , 33 ] MT expression in rat liver was also regulated by cAMP and glucocorticoids. [ 34 ] Similar to these results, we showed that dexamethasone mainly upregulated MT expression ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Obesity beginning in childhood is characterized by hyperplasia and hypertrophy, and adult-onset obesity is characterized by hypertrophy. MT1, MT2, and MT3 express in adipose tissue [ 14 ], and the expression of MT1 and MT2 in rodents is affected by nutritional status [ 15 ]. We previously reported that female MT1 and MT2 knockout (MTKO) mice developed high-fat-diet (HFD)-induced obesity, but that a standard diet did not induce obesity in the mice.…”
Section: Introductionmentioning
confidence: 99%